The Implementation of Project-Based Learning Model to Improve Students’ Skills in Writing Recount Texts - Mufidah, Noverisa Lailatul; Muhtarom; Datik, Aisyiyah Munawar (ICONELT, 2024)
This study investigates how the implementation of Project Based Learning (PjBL) affects in improving students’ skill level in expressing their ideas on recount text material in grade 8 UPT SMPN 2 Gresik. This study took samples from 31 students of class 8D UPT SMPN 2 Gresik. Therefore, data collection instruments included student skill tests through writing assignments. The results of this study showed a significant improvement in students’ skills. In addition, they showed a positive response to the application of the PjBL model in learning. In conclusion, students’ abilities to recall information from recount texts are significantly enhanced by the PjBL learning approach.